Physicochemical, Organoleptic Evaluation and Shelf Life Extension of Quinoa Flour-Coated Chicken Nuggets - Sobhy A. El-Sohaimy; Miral G. Abd El-Wahab; Zilolakhon A. Oleneva; Abduvali D. Toshev (Journal of Food Quality)
The objective of the current study was to develop innovative quinoa-coated chicken nuggets by using quinoa flour instead of wheat flour and evaluate the impact of this substitution on the shelf life of the product and its nutritional and sensorial stability. The evaluation of the product has been done through physiochemical and microbiological analysis every three days of the storage period compared with negative control (NC) and positive control (BHT) through 24 days of cold storage (4 ± 1°C). During storage, the quinoa flour-coated chicken nuggets showed the best ability for delay of lipid oxidation with a lowest TBARS value of 1.07 mg MDA/kg compared to negative control (NC) (2.39 mg MDA/kg) and positive control (BHT) (2.00 mg MDA/kg). The same trend was observed in protein oxidation, where the quinoa flour was able to retard the protein oxidation better than negative and positive control (BHT) where it showed a carbonyl content of 6.44, 5.39, and 4.20 nmol carbonyl content/mg protein, respectively. The quinoa-coated chicken nuggets showed the lowest microbial load (5.8 × 103 cfu/g) compared to negative and positive controls (1.8 × 105 and 3.8 × 104 cfu/g) at 24 days of cold storage. These findings could be emphasized such that the utilization of quinoa flour in the coating of chicken nuggets is more effective in retarding lipid and protein oxidation, furthermore preventing microbial contamination during cold storage. All these findings might be playing a crucial role in the extending of the shelf life of the product in addition to giving the product a pleasant taste and flavor to consumers.